What if Christopher Smart’s Cat Responded? A Human-Animal Studies Perspective on Jubilate Agno’s Cat Jeoffrey - Ożarska, Magdalena (Humanimalia, 2016)
The paper revisits Christopher Smart’s Cat Jeoffry section of Jubilate Agno (1759-1763) using a Human and Animal Studies research perspective. The issues discussed include the concept of pethood as embraced by the poet, with special focus on the cat’s name and its significance. Traces of the animal’s Derridean “gazing” at and responding to the human are sought, as is evidence of Dominique Lestel’s “thinking hairy” on the part of Smart the poet.